HUBUNGAN ANTARA KOMUNIKASI INTERN DENGAN EFEKTIVITAS KERJA PEGAWAI PADA BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN KUTAI BARAT - Lovitasari, Christiani (PREDIKSI, 2016)
Cristiani Lovitasari, the relations between the Internal Communication with the effectiveness of the employees work at Pada BadanPerencanaan Dan Pembangunan DaerahKabupatenKutai Barat. Under the guidance of the mother Salasiah, S. Sos, M. The as the mentor I and IbuDra.Hj.NanikPujiastuti, M. Si, as the mentor IIthis research aims to find out whether the Internal Communication has a positive relationship with the effectiveness of the employees work at Pada Badan Perencanaan Pembangunan Daerah KabupatenKutai Barat..The results of the study showed that there is a positive and significant relations between the Internal Communication variable with a variable effectiveness of employees work at Pada BadanPerencanaan Pembangunan Daerah Kabupaten Kutai Barat. This can be known from the results of statistical tests where the drag coefficient relationships (r) was 0,832 which means there is a very strong relationship between the two variables.Meanwhile test results t (t-test) shows that the t empirical produced is of 4,862. If the result being compared with table prices of critical t for n - 2 is 1,734. It means that there is a relations and the influence of the person that is significant from the Internal Communication variable against a variable effectiveness of employee work. Therefore it can be said that the purpose of this research can be achieved, problems can be solved and the hypothesis can be proved.